Surveillance of Climate-smart Agriculture for Nutrition (SCAN): Innovations for monitoring climate, agriculture and nutrition at scale - Rosenstock, Todd S.; Lamanna, Christine; DeRenzi, Brian; Chesterman, Sabrina; Kadiyala, Suneetha; Ng'endo, Mary; Chibuye, Kayokwa; Choga, Ngonidzashe; Wijk, Mark T. van (2016)
Climate change will affect the ability to deliver not only the quantity but also the type and quality of food necessary for nutritious diets. Global and regional 'climate-smart agriculture' initiatives offer an opportunity to mitigate climate impacts and improve nutrition outcomes at scale. The Surveillance of Climate-smart Agriculture for Nutrition (SCAN) project develops new way to acquire, integrate and analyze data to determine what is climate-smart and nutrition-sensitive.